2018
DOI: 10.1111/jdi.12876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium–glucose cotransporter 2 inhibitors in addition to insulin therapy on cardiovascular risk factors in type 2 diabetes patients: A meta‐analysis of randomized controlled trials

Abstract: The results showed that in the intervention group, greater reductions were achieved for blood pressure, glucose control, uric acid and bodyweight. This treatment regimen might therefore provide beneficial effects on the occurrence and development of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Studies have revealed that SGLT‐2 inhibitors could reduce the SUA levels of patients with both T2DM and hyperuricaemia 11,15 . To the best of our knowledge, only a few systematic reviews and meta‐analyses have evaluated the effectiveness of SGLT‐2 inhibitors in reducing the SUA levels of patients with T2DM 10,14,16 . Moreover, no comparative analysis of the effects of different SGLT‐2 inhibitors on lowering SUA levels has been made, let alone the optimal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that SGLT‐2 inhibitors could reduce the SUA levels of patients with both T2DM and hyperuricaemia 11,15 . To the best of our knowledge, only a few systematic reviews and meta‐analyses have evaluated the effectiveness of SGLT‐2 inhibitors in reducing the SUA levels of patients with T2DM 10,14,16 . Moreover, no comparative analysis of the effects of different SGLT‐2 inhibitors on lowering SUA levels has been made, let alone the optimal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium‐glucose co‐transporter 2 (SGLT‐2) inhibitors are a novel class of antidiabetes agents that are independent of insulin release and action 14 . These drugs reduce plasma glucose levels by decreasing the renal reabsorption of glucose and increasing the excretion of urinary glucose 15,16 . In addition, SGLT‐2 inhibitors are characterized by the additional benefits to address unmet clinical needs, such as weight loss, blood pressure control, lipid‐lowering effects and reduced cardiovascular risk factors 15,17–19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al assessed the impact of SGLT2i as an add-on treatment to insulin therapy compared to the control group in patients with T2DM, which received a placebo in addition to insulin. They calculated MD of SUA change -26.16 μ mol/L (95% CI [-42.14, -10.17], I 2 = 80%) through assessment of 5 comparisons [ 78 ]. Yumo Zhao et al specifically focused on SUA changes of 62 trials, which compared the effects of SGLT2is with placebo or active control or standard care.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis of randomized control trials that studied the effect of dipeptidyl peptidase‐4 inhibitors in addition to insulin treatment in patients with type 2 diabetes, improved glycemic control without an increased risk of hypoglycemia or weight gain compared with insulin treatment alone was reported 9 . In contrast, in a meta‐analysis of randomized control trials that investigated the effect of SGLT2i in addition to insulin treatment on cardiovascular risk factors in patients with type 2 diabetes, better glycemic control and greater reductions of blood pressure, uric acid, bodyweight and daily insulin doses compared with insulin treatment alone were reported 10 . These effects of SGLT2i might provide beneficial effects to suppress cardiovascular events, but the increased risk of hypoglycemia, and urinary tract and genital infection related to SGLT2i should be of note.…”
Section: Impacts Of Newly Developed Insulin Analogsmentioning
confidence: 99%